Answer:
The answer is C
Step-by-step explanation:
did the test on edg
200t + 8t^3 - 80t^2
8t(25 + t^2 - 10t) ....rearrange
8t(t^2 - 10t + 25)
8t(t - 5)(t - 5)
8t(t - 5)^2 <==
One possible solution is
f(x) = x^4
g(x) = x-3
Since
f(x) = x^4
f(g(x)) = ( g(x) )^4
f(g(x)) = ( x-3 )^4
=================================================
Another possible solution could be
f(x) = x^2
g(x) = (x-3)^2
Because
f(x) = x^2
f(g(x)) = ( g(x) )^2
f(g(x)) = ( (x-3)^2 )^2
f(g(x)) = (x-3)^(2*2)
f(g(x)) = (x-3)^4
Opposite conjugate.
(-1/3) is (3/1)